SCHOOLOGY AND ITS CONTRIBUTION IN ENGLISH LEARNING - Astuti, Epata Puji (Universitas Muhammadiyah Semarang, 2019)
Education in Industrial Revolution 4.0 increases the demand of online learning. In this era almost all aspects of human’s life change into digital. Education tries to find the alternative of traditional teaching and tries to more engage with digital world. Education needs a tool that can connect teacher and students inside and outside the class, a tool which is more familiar with the student’s life. Schoology is a kind of social networking Learning Management System that offers the easy access for student to connect with their lecturer and vice versa. They can learn the material from lecturer everywhere just by clicking on their mobile phone. The use of Schoology supports not only students but also the teacher in English learning. By the Schoology teacher can create paperless culture in education, give online assignments and online assessments to the students even connect in discussion with other lecture about certain topic.